Analysis of the Implementation of SP4N-LAPOR Policy as a Form of Public Service Reporting Mechanism at Diskominfo of Southeast Sulawesi Province: Analisis Implementasi Kebijakan SP4N-LAPOR Sebagai Bentuk Mekanisme Pelaporan Layanan Publik Di Diskominfo Provinsi Sulawesi Tenggara - Andi Fatwa Mahdika Candra; Hartono, Supri; Ilman, Ghulam Maulana (Yayasan Sagita Akademia Maju, 2025)
E-government implementation is a strategic step to create transparent, accountable and efficient governance. One of the main programs that support this achievement is SP4N-LAPOR (National Public Service Complaint Management System), a digital platform that provides access to the public to convey aspirations and complaints related to public services. This research focuses on analyzing the implementation of the SP4N-LAPOR policy at the Diskominfo of Southeast Sulawesi Province, using Edward III's policy implementation theory based on four assessment indicators Communication, Resources, Disposition, Bureaucratic Structure to identify the effectiveness of its implementation and reveal supporting and inhibiting factors. The results showed some significant challenges in implementing this policy. From the communication aspect, the lack of socialization has led to a lack of understanding among the public and government officials regarding the mechanism of using SP4N-LAPOR. Limited resources, both in terms of the quality of human resources and budget, are also an obstacle. The fragmented bureaucratic structure and lack of coordination between agencies exacerbate the situation. In addition, the non- uniform attitude of policy implementers or disposition shows that some agencies have not prioritized the use of this platform. However, there are also supporting factors, such as national regulations that support the implementation of SP4N-LAPOR, governor instructions, and the availability of digital systems that facilitate the management of public reports. This study concludes that SP4N-LAPOR implementation in Southeast Sulawesi still needs improvement. The low report completion rate indicates the need to strengthen human resources through training, budget increases, and more equitable development of information technology infrastructure. Socialization to the community must also be improved to encourage active participation in reporting complaints. This research not only makes a theoretical contribution to the study of E-government policy implementation but also offers practical recommendations to improve public complaint management.